A Survey On Cloud Computing and Its Various Services (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Cloud computing is a hot topic all over the world nowadays, through which customers can access information and computer power via a web browser. As the adoption and deployment of cloud computing increase, it is critical to evaluate the performance of cloud environments. Currently, modeling and simulation technology has become a useful and powerful tool in cloud computing research community to deal with these issues. Cloud simulators are required for cloud system testing to decrease the complexity and separate quality concerns. Cloud computing means saving and accessing the data over the internet instead of local storage. In this paper, we have conducted a survey on the models of cloud environment, benefits and issues related to it.